Sodium bicarbonate as a blowing agent on morphology and properties of conductive carbon black-filled epoxy porous prepared by emulsion system - Am Phan, Anusha Leemsuthep (School of Materials Engineering, Universiti Malaysia Perlis, 2017)
This research focuses on fabrication of conductive epoxy porous and its properties. The objectives of this project are ; to investigate the effect of emulsion temperatures on morphology, thermal properties of conductive epoxy porous (CEP); and its application as a conductive additive in epoxy-polyamine composites ; to study the effect of carbon black content as conductive filler on morphology, thermal properties of conductive epoxy porous (CEP); and the electrical conductivity of CEP- filled epoxy ; to study the effect of sodium bicarbonate content as blowing agent on foaming mechanism as well as on morphology, thermal properties of conductive epoxy porous (CEP) ; and its application as a conductive additive in epoxy-polyamine composites.